2018
DOI: 10.1088/1361-6528/aac372
|View full text |Cite
|
Sign up to set email alerts
|

A simple robust method of synthesis of copper–silver core–shell nano-particle: evaluation of its structural and chemical properties with anticancer potency

Abstract: A simple method of synthesis of a stable bimetallic copper-silver nano-particle (CuAg-NP) was developed by successive reduction of Cu(NO) and AgNO, using hydrazine hydrate as the reducing agent and gelatin and poly-vinyl pyrrolidone (PVP) as the capping agents. The round-shaped particles were of a core-shell structure with a core of Cu atoms surrounded by a shell of Ag atoms. The size and the mol. wt. of the NPs were (100 ± 10) nm and (820 ± 157) Kd, respectively; the particles were crystalline in nature and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 97 publications
3
16
0
Order By: Relevance
“…The blue shift in absorbance spectra is expected to the Cu NPs and redshift is expected to the Ag NPs. We found that the obtained results are in good agreement with the previous reports for Cu: Ag ratio [28][29][30]. The location of the precise metal NPs plasmon absorption band determines the shape and size of the NPs.…”
Section: Resultssupporting
confidence: 91%
“…The blue shift in absorbance spectra is expected to the Cu NPs and redshift is expected to the Ag NPs. We found that the obtained results are in good agreement with the previous reports for Cu: Ag ratio [28][29][30]. The location of the precise metal NPs plasmon absorption band determines the shape and size of the NPs.…”
Section: Resultssupporting
confidence: 91%
“…This early apoptotic cell population was greater than those reported for cancer cell lines treated with the Fe 2 O 4 @Ag nanocomposite (13.2%) [ 30 ] and Cu–Ag NPs (24.53%). [ 31 ] These results confirmed the changes in the mitochondrial membrane, which ultimately led to a loss of the membrane potential function. The late apoptosis percentage exposed by CuFe 2 O 4 @Ag NPs (Q 2 ) was 5.57% compared to 6.49% for the control cells.…”
Section: Resultssupporting
confidence: 58%
“…The vibration bands at 3444 and 3387 cm −1 could be attributed to primary amines (NH 2 ) [34]; the carboxylic acid (OH) stretch was located at 2936 cm −1 [35]. However, peaks at 2356 cm −1 could be assigned to C-H asymmetric stretching vibration for aliphatic groups [36]. Meanwhile, the spectral peaks in around 1644, 1636 and 1744 cm −1 implied the presence of -C=C bond [36].…”
Section: Fourier-transform Infrared (Ft-ir)mentioning
confidence: 99%